Them, us and me : how the Old Testament speaks to people today - Grey, Jacqueline (Sydney, N.S.W. : APS Press, 2008)
"This is a popular introduction to the way that Pentecostal Christians can read the Old Testament (Hebrew Bible) (Hermeneutics)."--Provided by publisher.
APSS vol. 2
Includes bibliographical references.
Keywords: Bible. Old Testament; Bible. Old Testament -- Commentaries; Bible. Old Testament -- Criticism, interpretation, etc